2019
DOI: 10.3390/plants8090352
|View full text |Cite
|
Sign up to set email alerts
|

Strigolactone Signaling Genes Showing Differential Expression Patterns in Arabidopsis max Mutants

Abstract: Strigolactone (SL) is a recently discovered class of phytohormone that inhibits shoot branching. The molecular mechanism underlying SL biosynthesis, perception, and signal transduction is vital to the plant branching phenotype. Some aspects of their biosynthesis, perception, and signaling include the role of four MORE AXILLARY GROWTH genes, MAX3, MAX4, MAX1, and MAX2. It is important to identify downstream genes that are involved in SL signaling. To achieve this, we studied the genomic aspects of the strigolac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 67 publications
2
11
0
Order By: Relevance
“…This was supported by the recent study that identified PhTCP3 (corresponding to PaTCP18c in this study) acting downstream strigolactone (SL) signaling to regulate lateral branching in petunia [51]. In addition, downstream genes in SL signaling have been identified using a microarray in Arabidopsis [68]. It is interesting to further investigate the molecular mechanism for petunia CYC1 group genes in SL pathway.…”
Section: Expression Patterns and Potential Functions Of Patcp Genessupporting
confidence: 69%
“…This was supported by the recent study that identified PhTCP3 (corresponding to PaTCP18c in this study) acting downstream strigolactone (SL) signaling to regulate lateral branching in petunia [51]. In addition, downstream genes in SL signaling have been identified using a microarray in Arabidopsis [68]. It is interesting to further investigate the molecular mechanism for petunia CYC1 group genes in SL pathway.…”
Section: Expression Patterns and Potential Functions Of Patcp Genessupporting
confidence: 69%
“…These hormones include strigolactone, cytokinin, and karrikin. Strigolactone (SL) is a recently discovered class of phytohormone that inhibits shoot branching [205]. ABA signaling may regulate SL biosynthesis [206].…”
Section: Other Aspects Of Aba Signalingmentioning
confidence: 99%
“…These hormone includes; Strigolactones, Cytokinin, and Karrikin. Strigolactone (SL) is a recently discovered class of phytohormone that inhibits shoot branching [189]. ABA-signaling might regulate SL biosynthesis [190].…”
Section: Other Aspect Of Aba Signalingmentioning
confidence: 99%